A complement of ten essential and pleiotropic arabidopsis COP/DET/FUS genes is necessary for repression of photomorphogenesis in darkness. - Kwok, S F (1996)
Two genetic screens, one for mutations resulting in photomorphogenic development in darkness and the other for mutants with fusca phenotype, have thus far identified six pleiotropic Arabidopsis COP/DET/FUS genes. Here, we characterized representative mutants that define four additional pleiotropic photomorphogenic loci and a null mutant allele of the previously defined DET1 locus. Dark-grown seedlings homozygous for these recessive mutations exhibit short hypocotyls and expanded cotyledons and are lethal before reaching reproductive development. Dark-grown mutant seedlings also display characteristic photomorphogenic cellular differentiation and elevated expression of light-inducible genes. In addition, analyses of plastids from dark-grown mutants reveal partial chloroplast differentiation and absence of etioplast development. Root vascular bundle cells of light-grown mutant seedlings develop chloroplasts, suggesting that these FUS gene products are important for suppression of chloroplast differentiation in light-grown roots. Double-mutant analyses indicate that these pleiotropic cop/det/fus mutations are epistatic to mutations in phytochromes, a blue-light photoreceptor, and a downstream regulatory component, HY5. Therefore, there is a complement of at least 10 essential and pleiotropic Arabidopsis genes that are necessary for repression of photomorphogenic development.